ANALISIS ECONOMIC ORDER QUANTITY TERHADAP PREDIKSI PERSEDIAAN (STUDI EMPIRIS PADA UMKM MANUFAKTUR DI KOTA BANDA ACEH) - Ningsih, Mely Beauty; BZ, Fazli Syam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
According to data from the Aceh Cooperative and the Office of Small and Medium Enterprises in the past three years, the number of small and medium enterprises has increased by 25%. The contribution of SMEs to Acehs GRDP reached 55.56%. Various programs have also been implemented to improve the performance of small and medium-sized enterprises. One of them is inventory management at the lowest cost. This study aims to determine the economic order quantity of raw materials and compare the total cost of raw material inventory, as well as the use of economic order quantity (EOQ) to carry out safety stock and reorder levels for manufacturing companies in Banda Aceh. EOQ is the best or most economic order quantity to be used according to the period cost.This study selected ten manufacturing MSME samples in Banda Aceh. It shows that the results of using the EOQ method to order cost information are different from the calculation of the strategy implemented by the company. The frequency of ordering raw materials used to be fixed at 12 times, but it has now been reduced to ensure ordering costs